Autoantibodies against ganglioside GM3 are associated with narcolepsy-cataplexy developing after Pandemrix vaccination against 2009 pandemic H1N1 type influenza virus. (September 2015) - Saariaho, Anna-Helena; Vuorela, Arja; Freitag, Tobias L.; Pizza, Fabio; Plazzi, Giuseppe; Partinen, Markku; Vaarala, Outi; Meri, Seppo
Abstract: Following the mass vaccinations against pandemic influenza A/H1N1 virus in 2009, a sudden increase in juvenile onset narcolepsy with cataplexy (NC) was detected in several European countries where AS03-adjuvanted Pandemrix vaccine had been used. NC is a chronic neurological disorder characterized by excessive daytime sleepiness and cataplexy. In human NC, the hypocretin-producing neurons in the hypothalamus or the hypocretin signaling pathway are destroyed by an autoimmune reaction. Both genetic (e.g. HLA-DQB1*0602) and environmental risk factors (e.g. Pandemrix) contribute to the disease development, but the underlying and the mediating immunological mechanisms are largely unknown. Influenza virus hemagglutinin is known to bind gangliosides, which serve as host cell virus receptors. Anti-ganglioside antibodies have previously been linked to various neurological disorders, like the Guillain-Barré syndrome which may develop after infection or vaccination. Because of these links we screened sera of NC patients and controls for IgG anti-ganglioside antibodies against 11 human brain gangliosides (GM1, GM2, GM3, GM4, GD1a, GD1b, GD2, GD3, GT1a, GT1b, GQ1b) and a sulfatide by using a line blot assay. Samples from 173 children and adolescents were analyzed: 48 with Pandemrix-associated NC, 20 with NC without Pandemrix association, 57 Pandemrix-vaccinated and 48 unvaccinated healthy children. We found that patients with Pandemrix-associated NC had more frequently (14.6%) anti-GM3 antibodies than vaccinated healthy controls (3.5%) ( P = 0.047). Anti-GM3 antibodies were significantly associated with HLA-DQB1*0602 ( P = 0.016) both in vaccinated NC patients and controls. In general, anti-ganglioside antibodies were more frequent in vaccinated (18.1%) than in unvaccinated (7.3%) individuals ( P = 0.035). Our data suggest that autoimmunity against GM3 is a feature of Pandemrix-associated NC and that autoantibodies against gangliosides were induced by Pandemrix vaccination. Highlights: Pandemrix vaccine induced autoimmunity against gangliosides, particularly against GM3. Anti-GM3 antibodies were associated with Pandemrix-related narcolepsy-cataplexy. Anti-GM3 antibodies associated with HLA-DQB1*0602 in vaccinated patients and controls. Acting as a viral receptor GM3 could make complexes with H1 and lead to immunization. No anti-GM3 antibodies were found in sporadic Pandemrix-unrelated narcolepsy.